A study on factors contribute to homelessness issue in Malaysia: A case study at Anjung Singgah YKN in Jalan Hang Lekiu, Kuala Lumpur / Bibi Atika Kamis and Nur Leyiana Ammeera Salama - Kamis, Bibi Atika; Salamat, Nur Leyiana Ammeera (Faculty of Administrative Science and Policy Studies, 2014)
Homelessness describes the condition of people without a regular residence. People who are homeless are most often unable to acquire and maintain regular, safe, secure, and adequate housing, or lack fixed, regular, and adequate night-time residence. Homelessness can be defined as having no land or shelter. It can be seen as a condition of detachment from society characterized by the lack of the affiliative bonds that link people into their social structures. Homelessness carries implications of belonging nowhere rather than simply having nowhere to sleep. Homelessness involves people who live overcrowded, insecure or substandard accommodation, those forced into involuntary sharing of shelter, or those subjected to high levels of noise pollution or infestation. Homeless including the persons who sleep in a public or private place not designed for use as a regular sleeping accommodation for human beings (Eugene Arthurs, 2008).